Population Structure and Spatial Distribution Pattern of Populus euphratica Riparian Forest Under Environmental Heterogeneity Along the Tarim River, Northwest China - Yusup, Asadilla; Halik, Ümüt; Abliz, Abdulla; Aishan, Tayierjiang; Keyimu, Maierdang; Wei, Jianxin (Frontiers in Plant Science, 2022)
Populus euphratica Oliv. (Euphrates poplar), as the dominant tree species of desert riparian forests along the Central Asian inland rivers, plays a critical role in protecting arid land ecosystems. In recent decades, climate change and excessive water resources utilization activities have led to the environmental degradation of desert riparian forests along the Tarim River in northwest China. Understanding the forest stand structure and spatial distribution pattern provide important guidance for monitoring forest dynamics in support of sustainable management. However, few studies have examined how riparian forests stand attributes differ in response to environmental heterogeneity. In this study, terrestrial laser scanning (TLS) was applied to acquire a total of 1648 individual P. euphratica tree’s 3D structure attributes within 18 plots along the upper, middle, and lower reaches of the Tarim River, which included tree height (TH), diameter at breast height (DBH), crown diameter (CD), crown projection area (CPA), stand density index (SDI), age structure ratios and spatial pattern. The results showed that the average tree segmentation and structure determination accuracies of TLS were 93.2% and 94.6%. From the upper to the lower reaches, the average TH and CD decreased by 3.8 m and 0.3 m, while the DBH increased by 4.2 cm. The SDI and CPA exhibited the following order: upper reaches (454 n ha-1, 82.3%) > middle reaches (382 n ha-1, 67.3%) > lower reaches (263 n ha-1, 39.1%), the differences were significant at 0.05 level. The population age structure changed from growing population in the upper reaches to stable population in the middle and a temporarily stable population in the lower reaches. The pair correlation g(r) function determined random distribution pattern in the upper reaches [g(r) = 1.2], an aggregated pattern in the middle [g(r) = 3.1] and lower reaches [g(r) = 9.7]. The decline in groundwater depth and soil moisture increased aggregated distribution pattern (R=0.67 and 0.56, P<0.05) of the P. euphratica along the mainstream of Tarim River. The results enrich our understanding of the current development stage of P. euphratica, which is important for optimizing management strategies and realizing the sustainability of floodplain ecosystems.